(untitled) (Journal of Libya for geographical studies, 2023)
Human understanding of nature and its environmental phenomena and geographical and climatic qualities made it able to evolve according to life needs that are in line with the changes that occur on those phenomena and qualities. From this point of view, people are trying to coexist with the development of the design of buildings so that they keep pace with the climatic changes in the world, as well as the development of materials used in construction such as reinforced concrete, glass spaces and others, as well as ventilation and heating methods, in addition to the insulators used to separate the inside and outside of the building. Due to seasonal changes during the year, the increase in temperatures in summer, the sharp decline in winter and the necessary need to use air conditioning systems in terms of heating and cooling in buildings to get a comfortable atmosphere. Hence the important role played by exterior walls and ceilings in the thermal insulation process, which in turn reduces the process of energy consumption as the development and restorations are made in the design of walls and ceilings that will be of high value for thermal insulation. The study aims to compare the architectural environment and the changes in the materials used in construction, designs and construction methods to the external environment of the building and the developments that took place to suit the climatic changes in the region.